(untitled) (Scientific journal of the Fergana State University, 2023)
In humans, the primary cognitive process is carried out with the help of the senses. The idea of ​​the world created by such knowledge is, of course, very important. But this alone is not enough for a complete understanding of the essence of the world, objects, events. In such a situation, ideas about abstract concepts - abstractions - will help. Without knowledge of abstraction, the essence of the object cannot be revealed, the scientific goal cannot be achieved. From this point of view, the study of abstract nouns is of interest to Uzbek linguists.